Forgiveness: Easy to Say but Hard to Do - Giri, Ro'iz Santria (Universitas Muhammadiyah Surakarta, 2022)
Forgiveness is a reduced desire to avoid the person who has hurt us, and a reduced desire to hurt or take revenge against the individual and is accompanied by increased compassion and desire to act positively towards the person who hurt us. The purpose of this study is to describe forgiveness as a form of action that is easy to say but becomes a difficult thing to do. The writing of this research uses library research or library research. In this study the researcher collected from journal articles, books and news related to forgiveness. The results of several studies obtained explain that forgiveness is something that is easy to say but becomes a very difficult thing to do. There are various factors that can influence forgiveness. The following are factors that influence the first apology, Cognitive Social Variables. Second, Attack Characteristics. Third, the Quality of Interpersonal Relations. Fourth, Personality Factor. One of the most effective ways to forgive is to develop empathy and forget the painful past.